End-Expiratory Occlusion Test to Predict Fluid Responsiveness Is Not Suitable for Laparotomic Surgery. (January 2020) - Weil, Gregoire; Motamed, Cyrus; Monnet, Xavier; Eghiaian, Alexandre; Le Maho, Anne-Laure
Abstract : BACKGROUND: The end-expiratory occlusion test predicts fluid responsiveness in ventilated intensive care patients; however, its utility in the operating room is questioned. We assessed end-expiratory occlusion test in laparotomic surgery for predicting volume expansion. METHODS: Forty-six patients were included in this study: stage 1 (n = 26) with an end-expiratory occlusion test of 15 seconds, followed by volume expansion, which consisted of 250 mL of colloid over 5 minutes and stage 2 (n = 20) with an end-expiratory occlusion test of 25 seconds followed by volume expansion. The last 10 patients had transdiaphragmatic pressures probed. Patients with an increase in cardiac index >15% after volume expansion were responders. Pulse pressure variation, stroke volume (SV) index, and cardiac index were analyzed. Receiver operating characteristic curves were established for changes in SV and pulse pressure induced by end-expiratory occlusion test and pulse pressure variation using the responders status for volume expansion as outcome. RESULTS: A total of 44 (38%) volume expansions were deemed responders. After end-expiratory occlusion test of 15 seconds, no hemodynamic variables were significantly increased. After end-expiratory occlusion test of 25 seconds, SV index increased in responders (37.1 ± 8.8 mL/m 2 after end-expiratory occlusion test of 25 seconds versus 35.7 ± 8.6 before; P < .0001). End-expiratory occlusion test could not discriminate responders from nonresponders. Only pulse pressure variation had significantly different area under the curve from that expected by chance (0.7 [0.57–0.81]; P = .002 for end-expiratory occlusion test of 15 seconds; and 0.78 [0.64–0.89]; P = .0001 for end-expiratory occlusion test of 25 seconds). After laparotomy, gastric pressure decreased significantly (4 [2.75–5] vs 2 [2–4] cm H2 O; P = .0417); no difference was noticed in the transdiaphragmatic gradient. CONCLUSIONS: End-expiratory occlusion test was not reliable to discriminate responders from nonresponders after volume expansion during laparotomic surgery.